2020
DOI: 10.1186/s12576-020-00777-8
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between olfaction and cognitive function in the elderly

Abstract: This study investigated the relationship between olfaction and cognitive function in 12 elderly people (age: 80.9 ± 1.6) living in the community. Olfactory function was assessed by the identification threshold for rose odor. Four cognitive measures consisting general cognitive ability assessed by Mini-Mental State Examination (MMSE), its sub-domains, and attentional ability assessed by drawing a line to connect the numbers consecutively (trail-making test part A; TMT-A), were assessed. Subjects with a higher o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…The TMT is not only sensitive to changes in cognitive function due to brain injury ( Reitan, 1958 ); it may also detect those that occur due to aging and education ( Hashimoto et al, 2006 ; Specka et al, 2021 ). The TMT is widely used in the evaluation of cognitive function in older adults, including evaluation indicators in intervention studies ( Jacobs et al, 2020 ; Suzuki et al, 2020 ), driving performance in older adults ( Vaucher et al, 2014 ), and studies examining the relationship between physiological indicators and attention function ( Uchida et al, 2020 ). Both TMT scores are sensitive to progressive cognitive decline associated with dementia ( Greenlief et al, 1985 ).…”
Section: Introductionmentioning
confidence: 99%
“…The TMT is not only sensitive to changes in cognitive function due to brain injury ( Reitan, 1958 ); it may also detect those that occur due to aging and education ( Hashimoto et al, 2006 ; Specka et al, 2021 ). The TMT is widely used in the evaluation of cognitive function in older adults, including evaluation indicators in intervention studies ( Jacobs et al, 2020 ; Suzuki et al, 2020 ), driving performance in older adults ( Vaucher et al, 2014 ), and studies examining the relationship between physiological indicators and attention function ( Uchida et al, 2020 ). Both TMT scores are sensitive to progressive cognitive decline associated with dementia ( Greenlief et al, 1985 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has also suggested that cholinergic neurons in the basal forebrain may explain the relationship between olfaction and attentional ability. 17 A line of research has suggested that the impairment of the cholinergic basal forebrain is related to both olfactory dysfunction and cognitive impairment, especially attention and memory. 49 Use of anticholinergic medication has been associated with greater brain atrophy and cognitive decline among cognitively normal older adults.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies examining neuropsychological function in older adults are mostly cross-sectional and have reported that olfactory function, specifically odor identification, is associated with global cognitive function, verbal memory, attention, executive function, fluency, psychomotor speed, and manual dexterity. 2,[17][18][19][20][21][22][23] Data on the relation between olfaction and longitudinal changes in domain-specific neuropsychological function are limited, especially in domains involving a motor component, such as psychomotor speed and manual dexterity. 24,25 To address prior limitations, in this study we examined associations of olfactory function with longitudinal changes in brain volumes and neuropsychological function over time in a sample of well-characterized community-dwelling adults from the Baltimore Longitudinal Study of Aging (BLSA).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the condition was found to be minimized in the presence of cholinesterase inhibitors. 15 People who showed olfactory loss were found to have a higher chance of the modification of disease state to show dementia symptoms. The olfactory impairment occurring in the early stages can hence be linked to the involvement of the cerebral cortex and, therefore, is applicable as a biomarker for assessment of patients with PD on the risk of the developing cognitive deficits and conditions like dementia.…”
Section: Methodsmentioning
confidence: 99%